2020
DOI: 10.1063/5.0021030
|View full text |Cite
|
Sign up to set email alerts
|

Dermal fibroblasts and triple-negative mammary epithelial cancer cells differentially stiffen their local matrix

Abstract: The bulk measurement of extracellular matrix (ECM) stiffness is commonly used in mechanobiology. However, past studies by our group show that peri-cellular stiffness is quite heterogeneous and divergent from the bulk. We use optical tweezers active microrheology (AMR) to quantify how two phenotypically distinct migratory cell lines establish dissimilar patterns of peri-cellular stiffness. Dermal fibroblasts (DFs) and triple-negative human breast cancer cells MDA-MB-231 (MDAs) were embedded within type 1 collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 70 publications
4
20
6
Order By: Relevance
“…Recent work by our group uses this multi-axis AMR system to measure collagen network stiffness heterogeneity and anisotropy surrounding dermal fibroblast and MDA-MB-231 malignant mammary epithelial cells cultured within collagen gel (21). This study used two-axis AMR for the measurement of material property anisotropy in the fibrillar network of a fibrin gel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by our group uses this multi-axis AMR system to measure collagen network stiffness heterogeneity and anisotropy surrounding dermal fibroblast and MDA-MB-231 malignant mammary epithelial cells cultured within collagen gel (21). This study used two-axis AMR for the measurement of material property anisotropy in the fibrillar network of a fibrin gel.…”
Section: Discussionmentioning
confidence: 99%
“…AMR. Measurements of fibrin resistance to deformation were conducted in acellular fibrin gels using an optical tweezers AMR system previously described (51) but modified to measure material properties along multiple axes (52), in which bead position is detected from backscattered laser beam illumination. For AMR measurements, fibrin gels were prepared at University of Minnesota using the same reagents as used for the cell related experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Several methods have recently been developed that can help shed light on this issue. For instance, optical micro-rheological techniques using tracer particles seeded in the tissue have been successfully employed to study local variations of the mechanical environment in the pericellular space [115]. Furthermore, metabolic labelling techniques based on the principle of click chemistry offer the opportunity to evaluate the dynamics of secreted extracellular components, while cytoskeletal dyes compatible with live microscopy offer the chance to observe cytoskeletal rearrangements during prolonged tissue culture [83].…”
Section: Relevance Of Tissue Physical Biology In Tissue Engineeringmentioning
confidence: 99%
“…Past research by our group has shown that 24 hours after hydrogel polymerization, cells alter local and peri-cellular stiffness by a few orders of magnitude, even on a single cell level 10 . Further, cells can promote distinct stiffness anisotropies which vary with cell line, T1C concentration and biochemical treatments 11 . Nonetheless, more comprehensive understanding of bi-directional relationship between cell behavior and ECM stiffness is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In the rst set of experiments, cells were cultured inside rat tail T1C hydrogels prepared at 4 different concentrations (1.0, 1.5, 2.0 and 3.0 mg/ml). AMR measurements were conducted 48 hours after sample preparation to investigate if local stiffness levels established by the cells are in uenced by the initial concentration of hydrogels or whether cells have a stiffness setpoint and remodel their local environment to promote stiffness levels they intrinsically prefer, as previously suggested by our group 11 .…”
Section: Introductionmentioning
confidence: 99%